Ancient Plant Glyoxylate/Succinic Semialdehyde Reductases: GLYR1s Are Cytosolic, Whereas GLYR2s Are Localized to Both Mitochondria and Plastids - Brikis, Carolyne J.; Zarei, Adel; Trobacher, Christopher P.; DeEll, Jennifer R.; Akama, Kazuhito; Mullen, Robert T.; Bozzo, Gale G.; Shelp, Barry J. (Frontiers in Plant Science, 2017)
Plant NADPH-dependent glyoxylate/succinic semialdehyde reductases 1 and 2 (GLYR1 and GLYR2) are considered to be involved in detoxifying harmful aldehydes, thereby preserving plant health during exposure to various abiotic stresses. Phylogenetic analysis revealed that the two GLYR isoforms appeared in the plant lineage prior to the divergence of the Chlorophyta and Streptophyta, which occurred approximately 750 million years ago. Green fluorescent protein fusions of apple (Malus x domestica Borkh.), rice (Oryza sativa L.) and Arabidopsis thaliana [L.] Heynh GLYRs were transiently expressed in tobacco (Nicotiana tabaccum L.) suspension cells or Arabidopsis protoplasts, as well in methoxyfenozide-induced, stably-transformed Arabidopsis seedlings. The localization of apple GLYR1 confirmed that this isoform is cytosolic, whereas apple, rice and Arabidopsis GLYR2s were localized to both mitochondria and plastids. These findings highlight the potential involvement of GLYRs within distinct compartments of the plant cell.